Consumer online communication of corporate social responsibility in the sin industry context: Cases in the global online gambling industry. - Kauko, Maiju (My University, 2014)
So-called sin industries are often related to harmfulness, unethical business, and unproductiveness. Nowadays, the alcohol, gambling, and tobacco industries are most often considered to be part of sin industries, which is also the context of this study. However, the definition of a sin industry is always related to time and culture. Despite the controversies of sin industries, there are studies that have shown that corporate social responsibility (CSR) engagement is even more important for sin industries than for normal industries and that CSR has a positive effect on firm value in sin industries. With CSR this study refers to an ideology where company takes mostly voluntary actions towards various groups of stakeholders and the environment. In other words, the company goes beyond the legal norms and regulations. In particular, the purpose of this thesis is to find out how companies, operating in the online gambling industry, communicate about their CSR actions to consumers at their web pages. The online environment is essential for this study as online gambling environment is a source of many controversies in comparison to the traditional gambling halls and casinos. These include, for example, greater accessibility, anonymity, and availability of the service. This study uses qualitative textual analysis as its approach, more precisely the discourse analysis. In addition, as this study focuses on large international companies and their actions, also case study approach will be presented. The cases studied are Mybet, Unibet, and Bwin.Party. In order to study the subject, elements from discourse analysis are combined with insights of essential CSR theories, and the specific characteristics of the online gambling industry. As a background for the framework, this study uses the framework of Du & Vieira (2012). After analyzing the discourses of CSR communication and CSR practices, it seems that all of the case companies still do not use all the potential that the online environment provides in terms of CSR or stakeholder communication. There are large differences between different communication tools used at different web pages (gambling pages vs. corporation pages) and between the firms’ CSR profiles. Moreover, there are large differences in the CSR practices used in the web pages of the case companies. The findings of this study are partially alarming as the case companies represent the largest companies in the industry. There are major varieties between the companies’ CSR communication and clear shortcomings in some parts of the online communication. Moreover, the trust of the consumer was broken in some places. If this is the standard that the biggest players in the industry have set with regards to CSR communication, it is probable that the smaller players are performing even worse. Moreover, the regulators are most likely concentrating on the larger companies, so the smaller companies might have fewer incentives and pressure to perform according to the regulations or exceeding the legislation. The conclusions of this thesis provide insights to managers, regulators, and scholars. Suggestions for future studies are provided as well.